Heat and mass exchanger analysis for Ree-Eyring hybrid nanofluid through a stretching sheet utilizing the homotopy perturbation method - F. Ali; A. Zaib; M. Faizan; S.S. Zafar; Shalan Alkarni; Nehad Ali Shah; Jae Dong Chung (Case Studies in Thermal Engineering, 2024)
An investigation is being carried out to describe the flow of a Ree-Eyring hybrid nanofluid by a stretch flow. SiO2 and GO are being examined for use as hybrid nanoparticles in the accumulation with carboxymethyl cellulose (CMC) water at low concentrations. A concentration of between 0.0 and 0.4 % is suggested for use as a base fluid (CMC− water). The model equations are firstly converted into ordinary differential equations through suitable alteration. The Homotopy Perturbation Method (HPM) and R–K method were applied to governing (ODEs). The produced results were identified by the R–K numerical technique. Both of these methods of approval demonstrate that our approach achieves an acceptable level of accuracy. The obtained results are numerical data for the behaviours of the velocity, temperature, and concentration of nanoparticles about other physical factors. Multiple graphs illustrating the conclusions of physical significance are shown and thoroughly analyzed. The most important findings from this research show that the stretching sheet has a role in determining the depth of the boundary layer. By raising the Weissenberg number, the thickness of the boundary layer will be enhanced, which will lead to an augmentation in the velocity of the non-Newtonian fluid. Moreover, the Prandtl number was a second crucial variable that was explored, it follows that enhancing the Prandtl number effect in a lessening in the thermal layer. The last parameter was the Schmidt number, and increasing in Schmidt number caused a significant reduction in the mass of the fluid.